(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper addresses an attempt made to capture the inherent variability in the deflection of reinforced concrete beams. For the study practical range of reinforced concrete beams with the span ranging from 3m to 10m and live load of 2knm2 to 5knm2. All the beams are sized for the required span and loading as per the directions of IS 4562000.Eexpression for deflection given in IS code is used as basic deterministic expression. Using statistical details mainly coefficient of variation and distribution model of various random variables involved in deterministic expression large number of deflection samples say ten thousand samples per beam are developed using Monte Carlo Simulation technique. Various statistical tests are conducted on sample developed and noticed that variability in deflection of reinforced concrete beam follows the lognormal distribution and coefficient of variation is consistent.